Post-Occupancy Evaluation (POE) theory room of SMK in Bantul assessed from lightning and ventilation - Nafisah, Durrotun; Munadi, Sudji; Adam, Nurul Suciana (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study Post-Occupational Evaluation (POE), aims to determine whether the natural lighting and ventilation openings in theoretical rooms at SMK XYZ have met the standards or not. The review of technical aspects focused on lighting and ventilation issues. This research is descriptive, evaluative, with the POE method at the investigative level, making 13 theoretical rooms as research objects and 156 students or 12 students per class as research subjects. The research instrument is a measuring instrument plus a questionnaire as data to strengthen the study results. Data collection techniques with observation and recording of primary data and secondary studies. The data analysis technique used descriptive quantitative. The condition of the theoretical space at SMK XYZ for the KBM process does not meet standards, such as natural lighting of the theoretical room in 11 of the 12 existing rooms; inlet and outlet area, the elevation of ventilation holes at the inlet throughout the theory room.